On the Identification and Characterization of Drought and Aridity in Postglacial Paleoenvironmental Records from the Northern Great Plains - Beaudoin, Alwynne (Géographie physique et Quaternaire, 2002)
AbstractThe Northern Great Plains region is especially sensitive to drought and is likely to be even more drought-prone under projected global warming. Drought has been invoked as an explanatory factor for changes seen in postglacial paleoenvironmental records. These proxy records may extend drought history derived from instrumental data. Moreover, in the last decade, some paleoenvironmental studies have been expressly undertaken for the examination of long-term drought history. Nevertheless, few such studies explicitly define drought. This makes it difficult to compare results or to understand what the results mean in terms of the operational drought definitions that are used in resource management. Operational drought is defined as usually short-term; longer sustained dry intervals reflect a shift to aridity. Therefore, high resolution paleoenvironmental proxies (annual or subdecadal) are best for the investigation of drought history. Such proxies include tree rings and some lake records. However, most lake-based records are sampled at lower resolution (decadal or subcentury) and are therefore providing aridity signals.